2017 Wilkins–Bernal–Medawar Lecture: why philosophy of science matters to science. (28th November 2018) - Massimi, Michela
Abstract : In an era where science is increasingly specialized, what is the value of interdisciplinary research? I argue that research across disciplinary boundaries plays a pivotal role in scientific inquiry, and it has a threefold value: it is exploratory ; it is unifying ; and it offers critical engagement . Philosophy of science is an interesting example of interdisciplinary research at the junction between the sciences and the humanities. What good can philosophy of science do for science? Despite anecdotal reports to the contrary, philosophy of science can in fact do important work for science. When it comes to critical engagement, I highlight what I call the social function of philosophy of science and I illustrate it with three examples taken from contemporary debates about evidence, progress and truth in science. A socially responsible philosophy of science—which is not afraid to speak up for evidence, progress and truth in science—best serves the needs of science in a tolerant, pluralist and democratic society.